2010
DOI: 10.1007/978-1-4419-5913-3_66
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Communication Flow Between Alzheimer Patients, Caregivers, and Neuropsychologists

Abstract: It is estimated that by 2050 over 100 million people will be affected by the Alzheimer's disease (AD). It not only affects the patient, but also the whole family and specially the caregiver, who is continuously under great stress conditions. We propose a software environment, called Mnemosine, designed to improve the quality of life of both Alzheimer patients and caregivers and to enhance the communication with the neuropsychologists. Mnemosine will provide them with resources that make easier the disease moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…With regard to the contextual components of QoL, such as facilities, infrastructure, or care, many technological disciplines have contributed to developing measures for enhancing the environmental quality of older adults. For example, several systems have been designed for improving QoL in Alzheimer’s disease patients and their families, including the international Smart Home for Elderly People (HOPE) project, in which the CETEMMSA Technological Centre (Barcelona) participated (Pilotto et al, 2011), or the Mnemosine system (Rodríguez-Rodríguez et al, 2010), aimed at increasing the QoL of both Alzheimer’s patients and their caregivers as well as enhancing communication with neuropsychologists. Other initiatives include the international Ambient Intelligence for Elderly (AmIE) project, the aim of which was to develop tools for the monitoring, control, and follow-up of older people through a system of alerts; and the Butler system, which is an e-health platform designed to improve the elderly population’s QoL (Etchemendy et al, 2011).…”
Section: Research On Aging In Spainmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the contextual components of QoL, such as facilities, infrastructure, or care, many technological disciplines have contributed to developing measures for enhancing the environmental quality of older adults. For example, several systems have been designed for improving QoL in Alzheimer’s disease patients and their families, including the international Smart Home for Elderly People (HOPE) project, in which the CETEMMSA Technological Centre (Barcelona) participated (Pilotto et al, 2011), or the Mnemosine system (Rodríguez-Rodríguez et al, 2010), aimed at increasing the QoL of both Alzheimer’s patients and their caregivers as well as enhancing communication with neuropsychologists. Other initiatives include the international Ambient Intelligence for Elderly (AmIE) project, the aim of which was to develop tools for the monitoring, control, and follow-up of older people through a system of alerts; and the Butler system, which is an e-health platform designed to improve the elderly population’s QoL (Etchemendy et al, 2011).…”
Section: Research On Aging In Spainmentioning
confidence: 99%
“…QoL is a good example of a geropsychology research aspect that satisfies the characteristics of aging research identified above, insofar as the assessment of QoL reflects population conditions (e.g., old age, healthy vs. disabled status, carers, community vs. institutionalized living) that must be taken into account since the needs of the elderly can change over time. questionnaire for assessing QoL in older adults living in different contexts (e.g., Fernández-Ballesteros & Zamarrón, 2007;González Sáenz de Tejada et al, 2011;Verdugo, Arias, Gómez, & Schalock, 2010); (3) to describe, compare, and predict QoL or QoL-associated variables in various contexts of older adults through descriptive and crosssectional studies, attending to characteristics such as socioeconomic status and educational levels (e.g., Otero-Rodriguez et al, 2011), community vs. residential settings (e.g., Fernández-Ballesteros et al, 1996), or health and illness (e.g., Lopes et al, 2007); and (4) to improve QoL regarding different conditions assessed by pre-post studies, for example, improving QoL in impaired people and their caregivers (e.g., Pilotto et al, 2011;Rodriguez-Rodriguez, Martel-Monagas, & Lopez-Rodriguez, 2010;Serra Rexach et al, 2009). All of these issues have been explored by different research fields.…”
Section: An Example: Quality Of Lifementioning
confidence: 99%